Reliable operation of a molecular-gap atomic switch in a vacuum achieved by covering with an ionic liquid. (1st May 2020) - Arima, Chisato; Naitoh, Yasuhisa; Shima, Hisashi; Akinaga, Hiroyuki; Hasegawa, Tsuyoshi
Abstract: Molecular-gap atomic switch, which operates by forming and dissolving a metal filament in a molecular layer between a solid electrolyte electrode and a counter metal electrode, is one of the potential devices to be used as a synaptic device in a brain-type computer. It is also expected to be used in a cosmic space such as in a satellite because of its high radiation resistance. However, it also has the issue that an operating bias increases in vacuum, which sometimes results in disabling the operation itself. We thought that desorption of moisture both from a molecular layer and from a solid electrolyte disables the operation. In order to prevent the desorption of moisture, we covered a switching area with an ionic liquid, which does not desorb even in vacuum. The new device structure shows a stable switching with an operating bias almost same as that in air.